Antibiograms, serotypes, and plasmid profiles of Pseudomonas aeruginosa associated with corneal ulcers and contact lens wear. - Mayo, M S (1986)
Pseudomonas aeruginosa was isolated from the corneal scrapings of 11 of 14 patients with gram-negative corneal ulcers and from salt tablet-prepared saline solutions from 6 of these patients wearing soft contact lenses. Comparison of physiological properties, antibiograms, serotypes, and plasmid profiles for five of the patients indicated that the isolates from the ulcer and the saline solution of a given patients were of the same strain. Improper hygienic practices of contact lens wearers appeared to be a major factor in the epidemiology of pseudomonad corneal ulcers.